Digital landscape architecture now - Amoroso, Nadia (London ; New York : Thames & Hudson, 2012)
Despite its importance to place-making, urban planning and the environment, landscape design has often played an inferior role to architecture. Coinciding with heightened social sensitivities, advances in material application, data-driven mapping techniques and digital technologies and construction methods, new practices in landscape design are producing a new wave of work around the world. This overdue publication presents work by the 50 most innovative practices across the globe. From dedicated landscape designers to architects turning their hand to the horizontal plane, an entirely new language of design is reshaping our gardens, public squares, leisure areas and business parks. A successor to Digital Architecture Now, this largeformat, highly visual publication is packed with inspirations and new spatial ideas for a world of more beautifully designed outdoors. -- Amazon Book Description.
Foreword -- Introduction -- Ballistic architecture -- Balmori -- Bradley Cantrell -- EcoLogicStudio -- Emergent -- Fletcher Studio -- Freise Brothers -- Groundlab -- GT2P -- Paulo Guerreiro -- Kathryn Gustafson -- Zaha Hadid -- Hargreaves Associates -- Hood Design -- Andrés Jaque Arquitectos -- Laboratory for Visionary Architecture -- LAND -- Land-I Architecture -- Landworks Studio -- Lateral Office -- Metagardens -- Meyer & Silberberg -- MLZ Design -- MVRDV -- Nox -- O2 Planning & Design -- Philip Paar, Jörg Rekittke -- Paisajes Emergentes -- PEG Office of Landscape & Architecture -- PYO Arquitectos -- R&Sie(n) -- Chris Speed -- StossLU - -TerreformONE -- Topotek1 -- Turenscape -- Urbanarbolismo -- VisionDivision -- West 8 -- Afterword.
boek
Keywords: Landscape design -- Computer-aided design; Landscape architectural drawing -- Computer-aided design; Architecture -- Computer-aided design; Architectural drawing -- Computer-aided design